The antifungal activity test of ointment and cream preparations of ”ketapang” (Terminalia cattapa L.) leaf on rabbit’s skin - Elinah Yuli Sukandar; Asep Gana Suganda; Gemi Utami Pertiwi (Indonesian Journal of Pharmacy, 2006)
Ketapang (Terminalia catappa L.) leaves has been used traditionally as skin infectious disease medicine, therefore ethanolic extract of ketapang leaves was formulated in ointment and cream preparations to be tested against fungi causing dermatomycosis i.e. Trichophyton mentagrophytes. The antifungal activity of both preparations was been tested in Trichophyton mentagrophytes infected rabbit’s skin. Result showed that ointment and cream containing 10 % extract were active against the fungi compared to the control. Healing occured on day 11.0 ± 3.0 in ointment treated rabbits, and ointment on day 12.7 ± 3.5 in cream treated rabbits, whereas in control healing occured on day 16.7 ± 6.6. Skin iritation index and eye irritation scores for ointment were 0.33 (maximum score 3) and 9.95 (maximum score 110) respectively, whereas those for the cream were 0.71 and 15.69, respectively.Key words: antifungal, Trichophyton mentagrophytes, ointment, Cream.